The Gravity in Unitary Quantum Theory (Global Journal of Science Frontier Research, 2023)
Abstract not found
Keywords: unitary quantum theory; general relativity; special relativity; maxwell equations; lorentz transformations; equation of john wheeler and bryce dewitt